Restitution in Social Reintegration of Human Trafficking Victims: An Islamic and Indonesian Criminal Law Perspective - Hasudungan Sinaga (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The crime of human trafficking has a significant impact and affects a large number of victims. This study examines the legal framework for protecting victims in Indonesia, analyzing these laws through the lenses of constitutionalism, natural law theory, and Islamic perspectives on restitution and social reintegration. The study used Natural Law theory to analyze the fundamental principles of justice that should guide the enforcement of restitution for victims of human trafficking. It also evaluated the alignment of Indonesian positive laws with principles of natural justice and the social reintegration of victims, using perspectives of constitutionalism and Islamic law. The research methods employed in this study included normative legal research, literature review, and qualitative analysis. The study found that Indonesian positive laws, such as Law No. 21 of 2007 and Law No. 1 of 2023, establish a comprehensive legal framework for the recovery and protection of human trafficking victims. However, they do not fully address the specific needs of victims, particularly in terms of psychological support. Evaluating based on constitutionalism and the concept of diyyah in Islam emphasizes the importance of financial compensation in recognizing the victims' suffering. Additionally, the concept of kafālah underscores the need for guaranteed protection, including social support, education, and social reintegration, to fully restore the dignity and well-being of victims. The study highlights the importance of community involvement in the reintegration process and advocates for legal reforms to enhance the effectiveness of the existing framework. These findings emphasize the need for an interdisciplinary approach in legal and policy frameworks to ensure the full recovery and reintegration of human trafficking victims.